Enhancing the Entrepreneurial Experience: A Supportive Environment For Sustainable Entrepreneurship Development In Slovenia - Ulčar, Lea; Marinčič, Dejan; Marič, Miha; Djurica, Maja (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
The paper discusses the strengthening of entrepreneurial experience through an effective supportive environment provided by the Republic of Slovenia. In cooperation with the Regional Development Agency of the Ljubljana Urban Region (RRA LUR), we investigated the existing PONI project, which promotes entrepreneurship. RRA LUR, as a coordinating agency of central Slovenian municipalities, contributes to coordinated economic development, sustainable mobility and efficient use of resources. By reviewing the effects of the PONI project, which operates within the framework of RRA LUR and aims to establish new companies that will be realized through entrepreneurial training by people with an entrepreneurial idea and a supportive environment for entrepreneurship, we have presented solutions for more effective support for business start-ups. The paper emphasizes the importance of creating a more stimulating entrepreneurial environment that facilitates starting a business and accelerates the economic development of Slovenia. In conclusion, we encourage the further development of knowledge and skills necessary for industrial change and sustainable progress.